2013
DOI: 10.1055/s-0033-1337122
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes, Morbidity, Mortality, and Fracture Healing in 58 Consecutive Patients with Geriatric Odontoid Fracture Treated with Cervical Collar or Posterior Fusion

Abstract: Controversy exists as to the most effective management option for elderly patients with type II odontoid fractures. The purpose of this study is to evaluate outcomes associated with rigid cervical collar and posterior fusion surgery. Patients with ≥ 50% odontoid displacement were treated with posterior fusion surgery including C1–2 (PSF group, n = 25, average age = 80 years). Patients with < 50% odontoid displacement were treated with a rigid cervical collar for 12 weeks (collar group, n = 33, average age = 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 29 publications
(54 reference statements)
3
13
0
Order By: Relevance
“…Molinari et al . also demonstrated a higher complication rate in the operative group (24% versus 6%) . This was confirmed in the current study, with a significantly higher rate of pneumonia, respiratory failure, cardiac arrhythmia and deep vein thrombosis in the operative group ( P < 0.05).…”
Section: Discussionsupporting
confidence: 87%
“…Molinari et al . also demonstrated a higher complication rate in the operative group (24% versus 6%) . This was confirmed in the current study, with a significantly higher rate of pneumonia, respiratory failure, cardiac arrhythmia and deep vein thrombosis in the operative group ( P < 0.05).…”
Section: Discussionsupporting
confidence: 87%
“… 2 , 9 , 11 Outcomes from this injury have shown to have high rates of morbidity and mortality and a poor prognosis regardless of the treatment. 12 , 15 24 Studies have described operative fixation of GOFs and have shown high rates of morbidity and mortality. 18 , 21 , 25 , 26 A less invasive treatment with a halo vest has been described with varying success.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 15 24 Studies have described operative fixation of GOFs and have shown high rates of morbidity and mortality. 18 , 21 , 25 , 26 A less invasive treatment with a halo vest has been described with varying success. 11 , 27 32 However, due to significant respiratory complications and increased morbidity, halo vests are not recommended in the elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…This matches with our results, as we did not find any difference related to sex, but the fusion was faster with younger patients in comparison to older ones. Additionally, Molinari et al 20 found poor results in geriatric patients even with rigid posterior fixation. All our cases were posttraumatic, so surgeries were done shortly after trauma.…”
Section: Journalmentioning
confidence: 99%